Good Demand-Supply Matching Practices as A Key to The Efficiency and Effectiveness of Free Nutritional Meal Programs: Leveraging Diverse Supply Sources to Maximize Government Expenditure Value - R. Beniadi Setiawan (Jurnal Indonesia Sosial Teknologi, 2024)
The free nutritious food program initiated by President-elect Prabowo and his cabinet aims to improve the quality of life of Indonesians, especially vulnerable groups. Various factors, including good demand and supply matching practices, largely determine the success of this program. The objective of this research is to analyze the best strategies and techniques for matching demand and supply, as well as for effective inventory management for this program. The research method used is qualitative, with data collection through literature study. After collecting the data, the analysis is done through several stages: filtering, data presentation, and conclusion drawing. The results show that good inventory management and supply-demand matching are key factors for the success of this program. Some strategies and techniques identified include careful planning, robust information systems, efficient supply chain management, good inventory management techniques, and diversification of supply sources. Diversifying supply sources helps the government reduce costs, improve food quality, support local economies, and strengthen national food security. By implementing these strategies, the government can ensure that the free nutritious food program can run efficiently and effectively and provide optimal benefits to the wider community.